Aspects of equivalence in two-dimensional resistivity imaging and modelling (2000)
The possibility for geoelectrical equivalence in two-dimensional (2-D) inversion of apparent resistivity data has been investigated. This involved the calculation of synthetic pscudosection data for simple geological structures using a finite difference approach. With the aid of statistical F-test, it is shown that identical or near-identical pseudosections can be generated from more than one 2-D model. In particular, the apparent resistivity pscudosection measured over2-D structures like basement fault, trough and horst resemble those arising from lateral variations In the overburden resistivity.